Comparison of low dose spinal anesthesia with general anesthesia in pre-eclamptic parturients undergoing emergency cesarean section - Sivevski, Atanas; SHoljakova, Marija; Andrijan Kartalov; Biljana Kuzmanovska; Durnev, Vesna (My University, 2015)
Objectives: Both spinal (SA) and general anesthesia (GA) are commonly used for operative management of pre-eclampsia parturients. Low dose SA is practical with faster onset and with fewer complications. This study aims to compare the effect of low dose SA or GA on neonatal wellbeing for preeclamptic par-turients undergoing emergency cesarean section Methodology: This prospective randomized study was carried out at University Clinic of Anesthesiology and University Clinic of Gynecology and Obstetrics at UCIM, Skopje, Republic of Macedonia. Sixty (n=60) pre-eclamptic parturients undergoing emergency cesarean section were divided in two groups receiving low dose spinal (SA) or general anesthesia (GA). Intra operatively we monitored and evaluated parturi-ents’ ECG, heart rate, noninvasive blood pressure, ephedrine requirement’s, as well as neonatal umbilical artery ( UA) blood gas samples and Apgar scores.Main outcome measure was a comparison of the influence of two different anesthesia methods (low dose SA vs. GA) on neonatal wellbeing, measured by umbilical artery (UA) blood gases, Apgar score and mark-ers of fetal hypoxemia with non-invasive hemodynamic status in 60 pre-eclampsia parturients undergoing non-elective (emergency) cesarean section (CS). Results: There was no statistical difference in the mean arterial blood pressure between the groups (90.6 ± 12.9 vs. 96 ± 8.9 mm Hg), as well as in the neonatal acid-base status and BE (p> 0.05). Spinal anes-thesia patients required more ephedrine (8,5 vs. 1.7 mg, p < 0.05). The Apgar score was ≥ 7 in 96% of newborns delivered after spinal anesthesia, while 75% after general anesthesia (p < 0.05).Conclusion We conclude that low dose spinal anesthesia can be safely used in pre-eclamptic parturients for emergency cesarean section (PDF) Comparison of low dose spinal anesthesia with general anesthesia in pre-eclamptic parturients undergoing emergency cesarean section. Available from: https://www.researchgate.net/publication/282304124_Comparison_of_low_dose_spinal_anesthesia_with_general_anesthesia_in_pre-eclamptic_parturients_undergoing_emergency_cesarean_section [accessed Sep 17 2020].
Keywords: Cesarean section; Spinal anesthesia; Apgar score; General anesthesia